The Global Financial Meltdown: Should Bonus Culture Take the Hardest Hit? - Wong, Mon Fong (2011)
This paper seeks to explore the claim by some critics that bonus culture in financial institutions is one of, if not the main catalyst of the recent global financial crisis. Many argued that excessive bonus payouts in Wall Street and some Western financial institutions have led to risky managerial decisions that threatened the highly integrated financial system when the US housing bubble collapsed. Though termed as a global financial meltdown, the crisis is in the strictest sense a financial crash that originated in some of the world’s most advanced economies and subsequently affected other countries. Notably, save for some trickle effects, the Asian financial sector has proved to be generally intact and stable during this period. This observation motivated me to investigate the actual role of bonus culture in the crisis by comparing the pay-performance relationship in US and UK financial institutions with those in selected East Asian countries. I found that in both Anglo-American and Asian financial institutions, there is significant relationship between total board pay and shareholder returns although the link is much weaker in Asia. In line with most studies, I also found significant pay-size relationship for both subsample and that the number of independent directors is significant in explaining Asian executives’ pay. I also ran separate regressions for firms above and below the median size for both subsamples. I found significant pay-performance linkage in all Anglo-American firms though it is slightly stronger in the larger firms. Such relationship is however absent in large Asian firms. On the contrary, return, firm size and the two governance proxies are important in explaining executive pay in smaller Asian firms. The findings on pay-performance sensitivity in Anglo-American and Asian firms led me to conclude that while executive compensation structure may have been one of the contributory causes of the crisis, it is by no means the main factor. Crudely put, Asian financial system is not characterized by excessive risk-taking amid significant pay-performance sensitivity. With this in mind, I urge all parties to instead focus on the root causes of the crisis such as the regulatory regime and the role to prevent such economic catastrophe from recurring. Also, while reform on executive remuneration is certainly needed, the attention should be on how to realign pay structure to match the firm’s risk management (i.e. by reducing pay-performance sensitivity especially in larger firms and to include other important considerations such as pay-risks) instead of restricting the level of pay.